Development of Flip Book-Based Learning Media for Sports Physiology in Physical Education Students at University - Sanusi Hasibuan; Indra Kasih; Dicky Edwar Daulay; Albadi Sinulingga; Muhammad Andri Fahrian (STAI Hubbulwathan Duri, 2024)
This study aimed to develop and validate flip book-based learning media for sports physiology at the Faculty of Sports Science, Medan State University, focusing on Recreational Health Physical Education students. The research utilized the ADDIE development model, encompassing Analyze, Design, Develop, Implement, and Evaluate stages. Data collection involved media expert validation questionnaires, materials, and trials with small and large student samples. Quantitative descriptive analysis was employed to present product development results, validate the tool, and assess its feasibility. Initial validation by a linguist resulted in a 76% suitability score, which improved to 89% after revisions, categorizing it as very feasible. Similarly, media experts rated the first stage at 76%, increasing to 89% post-revision. Small sample trials among students yielded a 76% suitability score, while large sample trials achieved 89%, both in the very feasible category. The findings indicate that flip book-based sports physiology learning media are highly suitable for use by physical education, health, and recreation students at Medan State University.